Environmental concern and environmentally responsible behaviour: Towards a model - Vivien Willers; Fred van Staden (Environmental Association of Southern Africa, 1998)
In this study, environmental concern has been conceptualised as the manifestation of attitudes that are directed at behavioural intentions of active personal involvement in caring about environmental matters. Based on a critique of theoretical approaches towards understanding the formation of environmental attitudes, a model has been developed where environmental concern acts as a precursor of responsible environmental behaviour. The emergence of environmentally concerned attitudes is depicted as a dynamic composition of transactions amongst individual subjective experiences, personal factors and structures at the socio-level. Attention is also paid to the temporal and situational embeddedness of environmentally concerned attitudes over time and space.